2019
DOI: 10.1002/hyp.13538
|View full text |Cite
|
Sign up to set email alerts
|

Variable power‐law scaling of hillslope Hortonian rainfallrunoff processes

Abstract: Hydrological studies focused on Hortonian rainfall–run‐off scaling have found that the run‐off depth generally declines with the plot length in power‐law scaling. Both the power‐law proportional coefficient and the scaling exponent show great variability for specific conditions, but why and how they vary remain unclear. In the present study, the scaling of hillslope Hortonian rainfall–run‐off processes is investigated for different rainfall, soil infiltration, and hillslope surface characteristics using the ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…The modified WEPP erosion theory is utilized to simulate the interrill and rill erosion processes. The similar form was utilized by WEPP (Flanagan & Nearing, 1995), Liu et al (2006), Tayfur (2007), An and Liu (2009), and Wu et al (2017, 2019). Note that, in the present model, the total widths of the interrill and rill areas are considered to vary along the hillslope, and the length and slope gradient of the representative rills vary accordingly in each longitudinal interval.…”
Section: Modeling Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…The modified WEPP erosion theory is utilized to simulate the interrill and rill erosion processes. The similar form was utilized by WEPP (Flanagan & Nearing, 1995), Liu et al (2006), Tayfur (2007), An and Liu (2009), and Wu et al (2017, 2019). Note that, in the present model, the total widths of the interrill and rill areas are considered to vary along the hillslope, and the length and slope gradient of the representative rills vary accordingly in each longitudinal interval.…”
Section: Modeling Approachmentioning
confidence: 99%
“…To extend the model to sloping surfaces, the governing equations were further modified by changing the terms depicting the gravity effect (Chen & Young, 2006;Wang et al, 2018;Wu et al, 2018). The detail of the soil infiltration model is showed in Wu et al (2018Wu et al ( , 2019.…”
Section: Hillslope Rainfall-runoff and Soil Erosion Model 221 Soil Infiltration Modelmentioning
confidence: 99%
“…Temporal intermittency of rainfall affects processes that influence the partitioning of rain between interception on plant canopies, evaporation, infiltration into soils, overland flow across the land surface, and other pathways. Intermittency influences the continuity of leaf wetness in vegetation communities (Binks et al, 2021), the change in soil moisture levels, and the related recovery of soil infiltrability that commences when rain ceases temporarily (Dunkerley, 2019; Poschlod et al, 2018; Wu et al, 2019), and the recovery of plant canopy interception capacity during intervals when evaporation can dry leaf surfaces and renew the leaf water‐holding capacity (Hadiwijaya et al, 2021; Iida et al, 2017). For estimating infiltration into the soil, it has been shown that the temporal resolution of the input rainfall data is important and that hourly data are only sufficient when the rainfall rate is low and/or the soils have low infiltrability (Fachi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%